The Ontology of Discontinuity - Bayrak, Selim (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
This paper aims to rethink the fundamental structure of existence through the lens of discontinuity. While discontinuity is often perceived as a lack or flaw, this study considers it an ontological necessity and a primordial condition of being. Existence is not shaped by continuity, but by ruptures, gaps, and disjunctions. Concepts such as infinity and nothingness cannot be understood without the framing power of discontinuity. Drawing inspiration from thinkers such as Deleuze, Bergson, and Heidegger, the text argues that discontinuity operates not only in physical reality but also in the realms of consciousness, language, knowledge, and meaning. In conclusion, discontinuity is not an external state of being, but a dynamic principle that underlies its structural continuity.